Decentralizing Governance Emerging Concepts and Practices - G. Shabbir Cheema , Dennis A. Rondinelli (ash institute for democratic governance and inn, 2007)
Few issues have created as much controversy over the past half century as how governments and political systems should be structured and how public policies should be made and implemented. Centralists generally believe that national political leaders and administrators know best how to provide security, promote economic growth, and maintain political stability. Those who argue for decentralization generally tend to have a more populist view. They tend to believe that the best public policies come from wide participation in public affairs and from local knowledge about how best to solve problems and meet the needs of citizens. Globalization has brought increasing interaction among governments, private enterprise, and organizations of civil society and, with it, increasing pluralism in shaping public policies both within and among countries. All three of these entities—governments, private enterprise, and civil society organizations—have come to be seen as institutions of governance, whose participation is crucial in mobilizing the knowledge and insight necessary to take advantage of the potential benefits of globalization and to mitigate or prevent its potential threats.